Intellectual Capital as a Determinant of Sustainable Profitability of Islamic Banks - Indrianasari, Neny Tri; Jariah, Ainun; Lukiana, Ninik (International Journal of Accounting and Management Research, 2025)
This study aims to examine the effect of Financing to Deposit Ratio (FDR) on the profitability of Islamic Rural Banks (BPRS) in East Java, with Intellectual Capital (IC) moderating variable. Using a quantitative approach, the study analyzes secondary financial data from 15 BPRS for the 2020–2023 period. Profitability is measured Return on Equity (ROE), while IC is assessed using the Value Added Intellectual Coefficient (VAIC™), which includes Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), and Structural Capital Value Added (STVA). The results indicate that FDR has a significant positive effect on ROE, implying that effective utilization of third-party funds through financing contributes positively to profitability. However, when IC is introduced as a moderating variable, the relationship between FDR and ROE becomes negative, suggesting that IC weakens the direct effect of FDR on profitability (quasi moderation). This indicates that high financing aggressiveness without strong intellectual capital may lead to increased risk and reduced profitability. The findings highlight the strategic role of IC consisting of human, structural, and relational capital in strengthening risk management and operational efficiency. Islamic banks are encouraged to invest in intellectual capital development to ensure sustainable profitability and competitive advantage in the long term.